Gambaran Tingkat Stres, Kecemasan, dan Depresi Mahasiswa dalam Persiapan Menghadapi Ujian Osce (Objective Structured Clinical Examination) - Indri Ramadini; Nova Yanti (Jurnal Sehat Mandiri, 2024)
The competency test is an assessment of the abilities of Indonesian nurse graduates using written test methods via Computer Based Test (CBT) and Paper Based Test (PBT) as well as the Objective Structured Clinical Examination (OSCE) method. The results of researchers' interviews with D3 Nursing and Nursing students found that almost 86% experienced anxiety and stress. The aim of this research is to identify the level of stress, anxiety and depression of students when facing the OSCE. The research design uses a descriptive method, the sample is 85 people (56 D3 Nursing students, 26 Nursing students). Scale. Results of analysis of student stress levels were 31.76% normal, 17.65% mild, 21.18% moderate, 12.94% severe, and 16.47% very severe. Analysis of student anxiety levels 38.82% normal .12% mild, 24.71% moderate, 10.59% severe, and 11.76 very severe. Meanwhile, analysis of depression levels was 56.47% normal students, 15.29% mild, 11.76% moderate, 3.53. % by weight, and 12.94% by weight. The conclusion of this research is that the level of stress, anxiety and depression among students is mostly at normal levels, but there are still students at severe and very severe levels. It is recommended that educational institutions carry out stress, anxiety and depression management to eliminate negative influences as a relaxation effort that can change the situation to neutral.